Growth of green catfish seed fed on sludge worm and artificial feed combination - Aryani, Netti; Pamungkas, Niken Ayu; Adelina, . (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This research aimed to obtain information of growth and survival of green catfish (Mystus nemurus) juvenile fed with sludge worm (Tubifex sp.; T) and artificial diet (PB) and added with the combination of 50% soybean pulp waste and 50% freshwater trash fish. Feeding was performed in several variation of time during 40 days of fish rearing. Average body length of juvenile was 12 mm and weight 2.8±0.0 mg, maintained at a density of 30 individuals/aquarium. The treatment in this research was T10PB30 (8–18 days old juvenile were fed with sludge worm and 18–48 days old fish were fed with artificial diet), T20PB20 (8–28 days old juvenile were fed with sludge worm and 28–48 days old were fed with artificial diet), T30PB10 (8–38 days old juvenile were fed with sludge worm and 38–48 days old were given artificial diet), PB40 (8–48 days old juvenile were fed artificial diet), T40 (8–48 days old juvenile were fed with sludge worm). The results indicated that the treatment of 40 days feeding with sludge worm provided the best growth and survival as daily growth rate of 16.4±28.0 g/day, the growth of the absolute length was 43.60±0.01 mm, the absolute body weight 2,047.2±35.0 mg and the survival rate was 96.44%. The best artificial feeding treatment was feeding with sludge worm for 30 days and with 10 days of artificial diet, results in daily growth rate of 4.53±0,25 mm/day, the growth of the absolute length 40.00±0.04 mm, the absolute body weight 1,447.2±15.0 mg, and the survival rate 94.44±2.60%. Keywords: artificial feed, sludge worm, growth, green catfish  ABSTRAK Penelitian ini bertujuan untuk mendapatkan informasi pertumbuhan dan sintasan benih ikan baung (Mystus nemurus) dengan pemberian cacing sutra (Tubifex sp.; T) dan pakan buatan (PB) kombinasi 50% limbah ampas tahu dan 50% ikan rucah air tawar. Pakan diberikan dengan variasi lama waktu berbeda selama pemeliharaan 40 hari. Rerata panjang awal benih adalah 12 mm dan bobot tubuh 2,8±0,0 mg, dipelihara dengan kepadatan 30 ekor/akuarium. Perlakuan dalam penelitian ini adalah T10PB30 (benih umur 8–18 hari diberi pakan cacing sutra dan umur 18–48 hari pakan buatan), T20PB20 (benih umur 8–28 hari diberi cacing sutra dan umur 28–48 pakan buatan), T30PB10 (benih umur 8–38 diberi pakan cacing sutra dan umur 38–48 diberi pakan buatan), PB40 (benih umur 8–48 hari diberi pakan buatan), T40 (benih umur 8–48 hari diberi pakan cacing sutra). Hasil penelitian ini menunjukkan bahwa perbedaan lama waktu pemberian cacing sutra dan pakan buatan yang terbaik adalah pemberian pakan cacing sutra selama 40 hari dengan laju pertumbuhan harian 16,4±28,0 g/hari, pertumbuhan panjang mutlak 43,60±0,01 mm, bobot mutlak 2.047,2±35,0 mg, dan sintasan 96,44%. Selanjutnya variasi lama waktu pemberian pakan buatan yang terbaik adalah pemberian cacing sutra selama 30 hari dan pakan buatan sepuluh hari dengan laju pertumbuhan harian sebesar 4,53±0,25 mm/hari, pertumbuhan panjang mutlak 40,00±0,04 mm, bobot mutlak 1.447,2±15,0 mg, dan sintasan 94,44±2,60%. Kata kunci: pakan buatan, cacing sutra, pertumbuhan, ikan baung